Estradiol Membrane-Initiated Signaling and Female Reproduction - Micevych, Paul E (Compr Physiol, 2015)
The discoveries of rapid, membrane-initiated steroid actions and central nervous system steroidogenesis have changed our understanding of the neuroendocrinology of reproduction. Classical nuclear actions of estradiol and progesterone steroids affecting transcription are essential. However, with the discoveries of membrane-associated steroid receptors, it is becoming clear that estradiol and progesterone have neurotransmitter-like actions activating intracellular events. Ultimately, membrane-initiated actions can influence transcription. Estradiol membrane-initiated signaling (EMS) modulates female sexual receptivity and estrogen feedback regulating the luteinizing hormone (LH) surge. In the arcuate nucleus, EMS activates a lordosis-regulating circuit that extends to the medial preoptic nucleus and subsequently to the ventromedial nucleus (VMH)—the output from the limbic and hypothalamic regions. Here, we discuss how EMS leads to an active inhibition of lordosis behavior. To stimulate ovulation, EMS facilitates astrocyte synthesis of progesterone (neuroP) in the hypothalamus. Regulation of GnRH release driving the LH surge is dependent on estradiol-sensitive kisspeptin (Kiss1) expression in the rostral periventricular nucleus of the third ventricle (RP3V). NeuroP activation of the LH surge depends on Kiss1, but the specifics of signaling have not been well elucidated. RP3V Kiss1 neurons appear to integrate estradiol and progesterone information which feeds back onto GnRH neurons to stimulate the LH surge. In a second population of Kiss1 neurons, estradiol suppresses the surge but maintains tonic LH release, another critical component of the estrous cycle. Together, evidence suggests that regulation of reproduction involves membrane action of steroids, some of which are synthesized in the brain.